2008
DOI: 10.1152/ajplung.00463.2007
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of cGMP-induced relaxation of pulmonary veins of fetal lambs exposed to chronic high altitude hypoxia: role of PKG and Rho kinase

Abstract: The roles of Rho kinase (ROCK) and cGMP-dependent protein kinase (PKG) in cGMP-mediated relaxation of fetal pulmonary veins exposed to chronic hypoxia (CH) were investigated. Fourth generation pulmonary veins were dissected from near-term fetuses ( approximately 140 days of gestation) delivered from ewes exposed to chronic high altitude hypoxia for approximately 110 days (CH) and from control ewes. After constriction with endothelin-1, 8-bromoguanosine 3',5'-cyclic monophosphate (8-Br-cGMP) caused a similar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
1
19
1
Order By: Relevance
“…In particular, PKG can dilate vessels by promoting dephosphorylation of the myosin light chain kinase. This is achieved by phosphorylation and activation of the myosin light chain phosphatase (26,27,81). Furthermore, PKG inhibits RhoA activity, which is a key modulator of the Rho kinase pathway (27,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, PKG can dilate vessels by promoting dephosphorylation of the myosin light chain kinase. This is achieved by phosphorylation and activation of the myosin light chain phosphatase (26,27,81). Furthermore, PKG inhibits RhoA activity, which is a key modulator of the Rho kinase pathway (27,49).…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence indicates that there is enhanced eNOS expression (41,59), reduced sGC (41), and CO-mediated relaxation (41,59,60) but enhanced large-conductance Ca 2ϩ -activated K ϩ (BK Ca ) channel function (42). In fetal lamb, eNOS expression is unchanged (91), but PKG function is enhanced and cGMP function is reduced (26). The diversity in the dysfunctions and compensations associated with highaltitude gestation have led us to design a series of studies to test how prenatal chronic hypoxia affects early postnatal bradykinin-induced vasorelaxation.…”
mentioning
confidence: 99%
“…In previous work we showed that oxygen tension alters intrapulmonary vascular endothelial function by altering the relationship between caveolin-1 and nitric oxide synthase. 3 Other studies have shown effects of hypoxia on nitric oxide mediated reactivity of intrapulmonary veins and arteries 9,10,11 or on remodeling of intrapulmonary vessels. 12,13 Following the observation of Murata et al, (2001) 1 which suggests a stronger effect of hypoxia on vascular remodeling than on nitric oxide mediated vascular reactivity of intrapulmonary vessels, the present study reveals that pathological changes beyond the intrapulmonary vessels, at the extreme end of the pulmonary or bronchiolar trees and alveolar regions, may also be a major cause of disease induced by chronic hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…EDNO may cause pulmonary vasculature to relax by decreasing the cytosolic Ca 21 level resulting from PKG-dependent stimulation of Ca 21 -activated potassium channels, which leads to membrane hyperpolarization and Ca 21 influx suppression (25). EDNO may also cause pulmonary vasodilatation by reducing the sensitivity of myofilaments to Ca 21 via the PKG-dependent phosphorylation of the regulatory subunit of myosin light chain phosphatase at threonine-695 and -852 (Thr-695 and Thr-852, respectively, human sequence), which leads to increased dephosphorylation of the myosin light chain and reduced contractility (26,27). NO has been found to suppress the proliferation of pulmonary vascular smooth muscle through the inhibition of cell cycle progression at the G1/S transition, which results from an increased nuclear localization of p21 and p27 and decreased cyclin A expression (28).…”
Section: Edno As a Paracrine Regulatormentioning
confidence: 99%
“…The mRNA expression of ET-1 and the secretion of the peptide by the EC are inhibited by NO (69)(70)(71)(72)(73). In the SMC, NO may attenuate ET-1 induced contraction by the inhibition of Ca 21 influx and Ca 21 release from the sarcoplasmic reticulum and by the interference with RhoA-Rho kinase signaling in a cGMP-PKG-dependent manner (26,27). NOinduced generation of cGMP contributes to the inhibition of ET-1-induced mitogenic and hypertrophic responses (74).…”
Section: Edno As a Paracrine Regulatormentioning
confidence: 99%